2004
DOI: 10.1111/j.1365-3180.2004.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weed control treatments on weeds, seed yield, yield components and nodulation in winter lentil

Abstract: Good weed control is critical in winter lentil production. This study was conducted on the lentil cultivar Sazak 91 during the winter seasons of 1997-98 and 1998-99 to determine the most appropriate method for controlling weeds. Hand weeding (weed-free control), weedy control (inoculated), weedy control (uninoculated), hand hoeing once, hand hoeing twice, trifluralin, imazethapyr, linuron, prometryn, phenmedipham + desmedipham, trifluralin + hand hoeing and linuron + hand hoeing treatments were evaluated and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
1
9
1
2
Order By: Relevance
“…The poorest weed control was observed in plots treated with fomesafen or linuron, or in plots handweeded only once. Our results are inconsistent with the findings of Erman et al (2004) and Tepe et al (2004), who reported acceptable weed control in lentil with linuron. The difference in results with linuron may be due to the different composition of weeds that linuron can control, different soil types, and lentil production under irrigated vs. rain-fed conditions.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The poorest weed control was observed in plots treated with fomesafen or linuron, or in plots handweeded only once. Our results are inconsistent with the findings of Erman et al (2004) and Tepe et al (2004), who reported acceptable weed control in lentil with linuron. The difference in results with linuron may be due to the different composition of weeds that linuron can control, different soil types, and lentil production under irrigated vs. rain-fed conditions.…”
Section: Resultscontrasting
confidence: 99%
“…Weeds limit lentil production through competition for water, soil nutrients, light, and space (Brand et al 2007;Erman et al 2004). Weed interference has been documented to cause yield reductions of 14 to 100% (Elkoca et al 2004), 35 to 67% (Tepe et al 2005), 60 to 100% (Halila 1995), and 40 to 80% (Al-Thahabi et al 1994) in lentil.…”
mentioning
confidence: 99%
“…But, both herbicides showed poor control of Echinochloa crus-galli because they are mainly active against broadleaf weeds (Kostov, 2006). Prometryn, linuron and a combination of linuron + hand hoeing were found to be the most effective for control of broadleaf weeds in winter lentil throughout the investigation period (Erman et al, 2004). Constant control of predominant weeds during both years of investigation was recorded to metolachlor+metobromuron.…”
Section: Resultsmentioning
confidence: 93%
“…, 2007). Erman et al. (2004) evaluated several weed control methods in winter lentil, but on a conventional farm.…”
Section: Introductionmentioning
confidence: 99%